Metode Omnibus Dalam Pembentukan Undang-Undang Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Cipto Kuncoro (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2023)
The birth of a legal product in the form of Law Number 11 of 2020 concerning Job Creation has led to disagreement with its enactment by taking the judicial review route to the Constitutional Court. The decision stated that it was contrary to the 1945 Constitution of the Republic of Indonesia and did not have conditionally binding legal force as long as it was not interpreted as "revisions were not made within 2 (two) years since this decision was pronounced". This study aims to analyze the basis for using the omnibus method in the practice of forming laws and regulations in Indonesia and the implications of the Constitutional Court Decision Number 91/PUUXVIII/2020 for Law Number 12 of 2011 and the Job Creation Law. The type of normative legal research used in this research is a statutory approach, a case approach, and a conceptual approach in finding the basic rules in the 1945 Constitution of the Republic of Indonesia and Law Number 12 of 2011 in carrying out a formal review of the Job Creation Law. The results in this study are that the use of the omnibus law method in the practice of forming statutory regulations in Indonesia has been carried out for a long time, even since the Dutch East Indies government until now. It's just that what forms the basis for the practice of using the omnibus law does not refer to guidelines in law (the law on the omnibus law method) as standard, standard and definite guidelines, including the Job Creation Law which the Petitioners requested for a formal test to the MK with Case Number 91/PUUXVIII/2020. The implications of the Job Creation Law were declared conditionally unconstitutional. This means that the current status of the Job Creation Law is unconstitutional but temporary.